Viability cf implementing direct interest-free credit clearance system in Muslim countries - Jaafar, Syammon; Abdullah, Adam; Hassan, Rusni; Mydin Meera, Ahamed Kameel (IIUM Institute of Islamic Banking and Finance (IIiBF)., 2016)
This study aims to examine the possibilities of implementing direct interest-free credit clearance (DIFCC) system,which is one of the viable alternatives to solve the problems of contemporary currency system. The DIFCC, which is based ona netting system,has been implemented successfully by several countries in the conventional setting, not to replace the current fiat money system, but rather as a parallel complementary currency. In this system, the distribution of credit as money will not be monopolized by the commercial banks, rather the distribution ison a mutual basis as long as there are products or services that can be offered to others among the members. As such, the system is fairer compared to the fiat money system and is free from the prohibited elements in Islamic finance such as riba, gharar and maysir as it requires exchange of real goods and services. In the context of the Muslim countries, the negative socio-economic effects of using the fiat money will not allow the countries to attain the objectives of the Shari’ah(maqasid al-Shari’ah). This study discuss the viability of implementing the DIFCC model which essentially applies the concepts of muqasah (nett-off) and hiwalah (transfer), apart from assessing the Shari’ah-compliancy of the model to be implemented as an innovative product in Islamic finance.